Diagnostic Accuracy Of Spectral Doppler Ultrasound In Diagnosis Of Malignant Breast Lesions Taking Histopathology As Gold Standard - Mehwish Tabassum; Rabia Waseem; Manal Niazi; Zainab Riaz; Hamna Shakil; Wajeeha Anam (Journal of Rawalpindi Medical College)
Objective: To determine the diagnostic accuracy of Spectral Doppler Ultrasound in malignant breast lesions, taking histopathology as the gold standard.